Problems Faced by The Fisher Folks: - Anuja; Uthayakumar, S.S. (South Eastern University of Srilanka, 2019)
Fisheries industry is known to be a rapidly growing field at global level and a considerable amount of gross domestic product (GDP) contribution is received from fisheries industry in Sri Lanka. This study aims to analyze the problems faced by the fisher folks in Aliyavalai area, Maruthankeni division in Jaffna district. The general objective of the study is to identify the problems faced by the fisher folks and the specific objectives are to find out the methods of fishing and to discover the socio economic and political issues faced by them. Primary and secondary data related to the problems of fisher folks were collected from forty four fishermen via simple random and stratified sampling method and the questionnaire survey was administered to collect the primary data. The data obtained were analyzed through SPSS and Microsoft Excel software. Conclusion is made through descriptive explanations and the additional explanations are given by the assistance of charts, photographs and maps. Based on the analysis, it is emphasized that the fisherman in that particular region face the social issues such as poor educational level, poor health and medical facilities and lack of transport facilities and the financial issues such as problems in marketing, storage, preservation, illegal fishing methods, traditional fishing methods and the issues from the intermediates. Violation of fishing method is a political issue faced by them. Livelihood of the fisherman in this area is strongly affected by the above mentioned problems and therefore, as a solution, implementation of new plans, improving the fishing techniques and usage of novel instruments for fishing, effective and the dedicated participation of government, nongovernment organizations and vadamaracchi East Fisheries cooperative societies can help to overcome the issues addressed in this study. It will contribute to the livelihood improvement of the fishing folks and development of the particular region.
Keywords: Fisheries Industry; Ariyavalai Area; Livelihood; Fishing method